(untitled) (Contemporary Journal of Social Science Review, 2025)
This study assesses the environmental awareness, attitudes, and behaviours of journalists in Sindh, Pakistan, with emphasis on how cognitive, emotional, and demographic factors condition their engagement with sustainability. With a value-belief-norm (VBN) and Media Role theoretical grounding, the study also evaluates the influence of cognitive orientations, emotional responses, and personal values on pro-environmental behaviour. The study adopted a quantitative approach with a structured questionnaire administered to a sample of 150 journalists from ten districts of Sindh. The data were analysed in SPSS using descriptive statistics, Pearson correlations, multiple regression, and paired sample t-tests to test five hypotheses. The results show strong positive correlations between pro-environmental disposition and mental orientation (r = .62, p < .01) as well as with pro-environmental behaviour (r = .55, p < .01), therefore proving H1. Sustainability consciousness was a strong predictor of influencing mental orientation (r = .68, p < .01) to support H2. Emotional responses of fear and frustration were significant predictors of mental orientation (β = .51, p < .001), thereby supporting H3. Ironically, despite high awareness: A huge attitude-behaviour gap was existent (t = 6.83, p < .001), supporting H4. Demographics such as education, experience, and media type moderated behaviour outcomes (H5) whereby digital journalists and highly educated individuals exhibited more engagement. Such findings bear witness to the cognitive-emotional bases of sustainability among journalists but also uncover some systemic barriers to behavioural change. The study recommends a need for capacity-building, institutional support, and targeted policy interventions to enable journalists to report on and practice environmental sustainability.